Impact of Self-Reward Understanding and Stress Coping Strategies on Student Success in Completing Final Project - Nurbaiti, Renda Trinanda; Uyun, Muhamad (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
One of the learning tasks that requires strong academic writing skills and language proficiency is the thesis. In reality, mostly of students feel burdened and encounter various difficulties in working on their thesis, resulting in delays in completing their study period. This research aimed to determine the impact of understanding self-reward and stress-coping strategies on the success of students in completing their final thesis. The research adopts a quantitative approach. The study's subjects consist of 40 students selected using the simple random sampling technique. The collected data was analyzed using multiple regression hypothesis testing. The results of the multiple regression hypothesis test indicate that: (1) there was a significant relationship between self-reward and stress coping strategies and students' success in completing final thesis, as evidenced by the f-test with a p-value of 0.000 < 0.05. (2) There was a significant relationship between self-reward and the success of students in completing final thesis with a positive direction, as evidenced by the t-value of 3.725 > the t-table value of 2.026 with a p-value of 0.001; (3) There was a significant relationship between stress coping strategies and the success of students in completing final thesis with a positive direction, as evidenced by the t-value of 2.842 > the t-table value of 2.026 with a p-value of 0.007. The implications of this study provided a deep understanding of strategies to enhance student's success in completing thesis, particularly in the context of understanding self-reward and implementing stress-coping strategies.Salah satu tugas pembelajaran yang membutuhkan keterampilan menulis akademis dan keterampilan bahasa yang kuat adalah skripsi. Pada kenyataannya, tidak sedikit mahasiswa yang merasa terbebani dan mengalami berbagai kesulitan dalam mengerjakan skripsi yang berdampak pada kelambatan dalam penyelesaian masa studi. Penelitian ini bertujuan untuk mengetahui dampak pemahaman self-reward dan strategi coping stres pada keberhasilan dalam menyelesaikanan tugas akhir pada mahasiswa. Penelitian ini menggunakan pendekatan kuantitatif. Subjek penelitian berjumlah 40 orang mahasiswa dengan menggunakan teknik simple random sampling. Data yang terkumpul dianalisis dengan uji hipotesis regresi berganda. Hasil uji hipotesis regresi berganda menunjukkan bahwa: (1) ada hubungan yang signifikan antara self-reward dan strategi coping stres terhadap keberhasilan mahasiswa dalam menyelesaikan tugas akhir yang dibuktikan dari hasil uji f dengan nilai p sebesar 0,000 < 0,05. (2) ada hubungan yang signifikan antara self-reward terhadap keberhasilan penyelesaian tugas akhir mahasiswa dengan arah hubungan yang positif, yang dibuktikan dengan nilai t hitung 3.725 > t tabel 2.026 dengan nilai p = 0.001; (3) ada hubungan yang signifikan antara strategi coping stres terhadap keberhasilan penyelesaian tugas akhir mahasiswa dengan arah hubungan yang positif, yang dibuktikan dengan nilai t hitung 2.842 > t tabel 2.026 dengan nilai p= 0.007. Adapun implikasinya memberikan pemahaman yang mendalam terkait strategi untuk meningkatkan keberhasilan mahasiswa dalam menyelesaikan tugas akhir, khususnya dalam konteks pemahaman self-reward dan penerapan strategi coping stres.